[tex]N= \frac{28* a^{n+2}-56* a^{n+1}-84*a^{n}}{-7*a^{n-1}} [/tex]⇔
[tex]N=\frac{7*(4* a^{(n-1)+3}-8*a^{(n-1)+2}-12*a^{(n-1)+1})}{-7*a^{n-1}}[/tex]⇔
[tex]N=\frac{7*(4* a^{(n-1)}* a^{3} -8*a^{(n-1)}* a^{2} -12*a^{(n-1)}* a^{1} )}{-7*a^{n-1}}[/tex]⇔
[tex]N=-\frac{(7*a^{(n-1)})*(4* a^{3} -8* a^{2} -12* a)}{(7*a^{n-1})}[/tex]
Fractia de mai sus se poate simplifica cu: [tex] \\ 7*a^{(n-1)}[/tex] si obtinem:
[tex]N=(-1)*(4*a^{3} -8*a^{2} -12*a)[/tex]⇔[tex]\\N=(-4)*(a^{3} -2a^{2} -3a)[/tex]⇔
[tex]N=(-4)*a*( a^{2} -2a-3)=(-4a)*[ (a^{2}-1)-2a-2][/tex]⇔
[tex]N=(-4a)*[(a-1)*(a+1)-2*(a+1)][/tex][tex]=(-4a)*[(a+1)*(a-1-2)][/tex]
In final avem ca: [tex]N=(-4)*a*(a+1)*(a-3)[/tex]
Spor la studiu